The synergistic effects of microcredit access and agricultural technology adoption on maize farmer’s income in Kenya - Shadrack Kipkogei; Jiqin Han; Gershom Mwalupaso; John Tanui; Robert Brenya (PLoS ONE, 2025)
Addressing global food security demands urgent improvement in agricultural productivity, particularly in developing economies where market imperfections are perverse and resource constraints prevail. While microcredit is widely acknowledged as a tool for economic empowerment, its role in facilitating agricultural technology adoption and improving agricultural incomes remains underexplored. This study examines the synergistic effects of microcredit access and agricultural technology adoption on the incomes of maize farmers in Kenya. Using household-level data, we employ an endogenous switching regression framework to control possible endogeneity in access to microcredit. Our findings shows that microcredit access positively influences the adoption of advanced agricultural technologies. Key determinants, including marital status, use of fertilizer application, access to extension services, and cooperative membership, are identified as significant determinants of microcredit access. Notably, the Average Treatment Effect on the Treated (ATT) indicates a 40.52% increase in income among farmers who access microcredit, mainly driven by the timely adoption of high-quality seeds, improved agricultural technologies, and enhanced inputs. These results highlight microcredit’s role in promoting allocative efficiency and enhancing Total Factor Productivity (TFP) within agricultural systems. Robustness checks, including propensity score matching and sensitivity analyses, corroborate these findings. The study recommends the implementation of targeted financial policies and educational initiatives meant to promote credit access, encourage savings, and enhancing financial literacy, particularly for credit-constrained households. Integrating these measures could strengthen rural financial markets and drive sustainable agricultural development across the regions.